Carrageenan and Garlic Essensial Oil Edible Film as Protective Coating on Catfish Sausage - Eko Nurcahya Dewi; Lukita Purnamayati (Fisheries and Marine Science Faculty - Jenderal Soedirman University, 2019)
The edible film based on carrageenan containing garlic essential oil (GEO) at different concentration (0%; 0,2%; 0,4%; and 0,6%) were added into carrageenan edible film (CEF) then applied on sausage, chilled storage for 10 days. The antioxidative allicin prevention on product determined its chemical characteristics such as TBA, TVBN, Aw, and pH. The addition of garlic essential oil on carrageenan based edible film was not significantly different on tensile strength. CEF with 0,6% of garlic essential oil produced the highest elongation value and the lowest Water Vapor Transmission Rate with the amount of 3,970% and 0,673%; respectively. The catfish sausage coated with 0,4% CEF produced TBA and TVBN value during chilled storage with the amount of 0,870 mg malonaldehyde/kg and 17,223 mgN/100g; respectively and not significantly different to CEF 0,6%. The result indicated that edible film containing garlic essential oil able to retard the oxidation process. Indicated from FTIR test, 0,2%; 0,4%; and 0,6% CEF containing garlic compound illustrated with S-S, N-H, C=O and C-H functional group with the wavelength of 408,91 cm-1, 925,83 cm-1, 1543,05 and 2931,8 cm-1.; respectively.